Maritime Weather Prediction using Fuzzy Logic in Ternate Waters North Maluku - Sangadji, Anisa; Aisjah, Aulia Siti; Nugroho, Gunawan (IPTEK The Journal for Technology and Science, 2016)
Ternate waters of North Maluku is one of Indonesian eastern waters whose maritime weather is often unpredictable. Weathers prediction is important to avoid accidents in the waters. The aim of this research is to obtain              a predictor model of wave’s height and current’s speed suitable for the Ternate waters using Takagi-Sugeno fuzzy logic. The data used is data from BMKG Maritime of Bitung which recorded per 6 hours during 5 years from July 2010 – June 2015. In order to reach accuracy of > 85%, 3 model predictor’s that used waves height and current speed are predictor Model A, Model B and Model C. Each model uses different input and total membership function. The result of this research shows that the Model C is the best model for Ternate waters. Model C uses 4 membership functions for 3 input variables. Inputs of waves height predictor consist of the actual wind speed (U(t)), actual waves height (H(t)) and waves height 6 hours ago (H(t-6)) and accuracy percentage of waves height 6 hours ahead (H(t+6)) is 91,99%; while inputs of current speed predictor consist of actual wind speed (U(t)), actual current speed (Cu(t)) and current speed 6 hours ago (Cu(t-6)) and accuracy percentage of current speed 6 hours ahead (Cu(t+6)) is 81,63%.